2021
DOI: 10.3390/jimaging7090190
|View full text |Cite
|
Sign up to set email alerts
|

A Bottom-Up Review of Image Analysis Methods for Suspicious Region Detection in Mammograms

Abstract: Breast cancer is one of the most common death causes amongst women all over the world. Early detection of breast cancer plays a critical role in increasing the survival rate. Various imaging modalities, such as mammography, breast MRI, ultrasound and thermography, are used to detect breast cancer. Though there is a considerable success with mammography in biomedical imaging, detecting suspicious areas remains a challenge because, due to the manual examination and variations in shape, size, other mass morpholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 134 publications
(205 reference statements)
0
17
0
Order By: Relevance
“…Ozha, et al, 17 surveyed the different scientific methodologies and techniques to detect suspicious regions in mammograms, spanning from methods based on low-level image features to the most recent novelties in artificial intelligence (AI)-based approaches. This method proved a considerable success with mammography in biomedical imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Ozha, et al, 17 surveyed the different scientific methodologies and techniques to detect suspicious regions in mammograms, spanning from methods based on low-level image features to the most recent novelties in artificial intelligence (AI)-based approaches. This method proved a considerable success with mammography in biomedical imaging.…”
Section: Discussionmentioning
confidence: 99%
“…GANs (Generative Adversarial Networks) belong to the family of unsupervised deep learning algorithms capable of extracting hidden underlying properties from data and employing them in decision-making. The fundamental goal of a GAN is to develop new image samples (by a generator) that the discriminator will not be able to tell apart from the original ones (Both network branches compete against each other and gradually learn to produce better results) [ 49 ]. GANs are reliant on two main components, namely, generator and discriminator.…”
Section: Advanced Augmentation Techniquesmentioning
confidence: 99%
“…We found that transfer learning plays a substantial role in various deep learning algorithms based on our literature review. With a modest number of datasets, this method is useful in the medical arena [15,21]. Different existing models based on a short dataset with the CNN architecture and the transfer learning method have not been completely investigated till now.…”
Section: Related Work In the Domainmentioning
confidence: 99%